Question #6b8b3

2 Answers
Jan 18, 2018

x = -9x=9

Explanation:

The equation can be rewritten with a -11 in front of the (10-x)(10x) instead of just having a negative sign:

-3(3x+15)-1(10+X)=353(3x+15)1(10+X)=35

First, distribute the -33 to the numbers in the parentheses:

-9x-45-1(10+x)=359x451(10+x)=35

Then, distribute the -11 to the numbers in the parentheses:

-9x-45-10-x=359x4510x=35

Now you need to isolate all xx terms on one side so you can eventually solve for it - to do this, add 4545 and 1010 to both sides of the equation:

-9x-45-10-x +45 +10=35 +45 +109x4510x+45+10=35+45+10
-9x-x=35 +45 +109xx=35+45+10
-10x = 9010x=90

Divide both sides by -1010 to get x by itself:

(-10x)/-10 = 90/(-10)10x10=9010
x = -9x=9

So, x = -9x=9.

Jan 18, 2018

x=-9x=9

Explanation:

Order of operations is BEDMAS (or PEMDAS)

-3*(3x+15) + -1*(10 +x) =353(3x+15)+1(10+x)=35
Multiply each bracket

(-3*3x + -3*15) + (-1*10 + -1*x) =35(33x+315)+(110+1x)=35
(-9x-45) + (-10-1x)=35(9x45)+(101x)=35

Combine terms
-9x-1x -45-10=359x1x4510=35
-10x-55=3510x55=35

Solve
-10x-55+55=35+5510x55+55=35+55
-10x=9010x=90

(-10x)/-10=90/-1010x10=9010

x=-9x=9

Check by substituting into original formula
-3(3*-9+15)+ -1(10-9)=353(39+15)+1(109)=35
-3(-27+15)+ -1(10-9)=353(27+15)+1(109)=35
-3(-12)+ -1(1)=353(12)+1(1)=35
+36+ -1=35+36+1=35
35=3535=35 True